Pengaruh Angka Partisipasi Sekolah dan Kepadatan Penduduk Terhadap Laju Pertumbuhan Ekonomi di Jawa Barat Tahun 2012-2021 - Sayyid Mujaddid Fikri; Ima Amaliah (Bandung Conference Series: Economics Studies, 2023)
Abstract. West Java Province is an area with economic growth in the 5th place on the island of Java. In fact, the geographical location which is very close to the National Capital should encourage development which has a positive impact on the Economic Growth Rate. Based on this, this study aims to determine the effect of school enrollment rates and population density in West Java in 2012-2021. This type of research is descriptive quantitative, using panel data from twenty-seven cities/regencies in West Java Province in 2012-2021. The estimated model used is the Fixed Effect Model by looking at the effects of each sector. The results of the study partially show that the school enrollment rate has a negative effect on the rate of economic growth with a coefficient value of -0.196815, which means that if the school enrollment rate increases by one percent, it will reduce the rate of economic growth by 0.196815 percent. Inequality in the distribution of school participation is a factor in the minimal influence of APS on the rate of economic growth in every district/city in West Java. In variation, the school enrollment rate and population density variables have an effect of 12.9196 percent on the economic growth rate of West Java in 2012-2021. While the remaining 87.0804 percent is explained by other variables outside the model in this study. Abstrak. Provinsi Jawa Barat merupakan daerah dengan pertumbuhan ekonomi di urutan ke-5 di pulau Jawa. Padahal, letak geografis yang sangat dekat Ibukota Negara seharusnya mendorong pembangunan yang berdampak baik terhadap Laju Pertumbuhan Ekonomi. Berdasarkan hal tersebut, penelitian ini bertujuan untuk mengetahui pengaruh angka partisipasi sekolah dan kepadatan penduduk di Jawa Barat tahun 2012-2021.Jenis penelitian ini adalah deskriptif kuantitatif, dengan menggunakan data panel dua puluh tujuh Kota/Kabupaten di Provinsi Jawa Barat pada tahun 2012-2021. Estimasi model yang digunakan adalah Fixed Effect Model dengan melihat efek dari setiap sektor. Hasil dari penelitian menunjukkan secara parsial bahwa angka partisipasi sekolah berpengaruh negatif terhadap laju pertumbuhan ekonomi dengan nilai koefisien sebesar -0,196815 yang berarti bahwa jika angka partisipasi sekolah terjadi kenaikan sebesar satu persen, maka akan menurunkan laju pertumbuhan ekonomi sebesar 0,196815 persen. Ketimpangan dalam penyebaran partisipasi sekolah menjadi faktor minimnya pengaruh APS terhadap laju pertumbuhan ekonomi di setiap Kabupaten/Kota di Jawa Barat. Secara variasi, variabel angka partisipasi sekolah dan kepadatan penduduk berpengaruh sebesar 12,9196 persen terhadap laju pertumbuhan ekonomi Jawa Barat tahun 2012-2021. Sedangkan sisanya yaitu 87.0804 persen dijelaskan oleh variabel lain diluar model pada penelitian ini.